(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to know the effect of distance training programs in its dimensions (importance, components, reality, obstacles) on the performance of employees of the Technical College in Jeddah. The researcher relied on the descriptive and analytical method for its suitability for the subject of the study. The study community is based on (334) employees of the Technical College in Jeddah. The questionnaire was used as a tool to collect data and it was distributed to (133) male and female employees, who were selected in a simple random way, and number of (120) questionnaires were retrieved by 90%. The data were analyzed through the statistical program (SPSS). Statistical significance between the distance training programs and the performance of workers in light of the Corona pandemic (Covid 19) at the Technical College in Jeddah, as well as finding a direct relationship between the dimensions of the distance training programs represented in (importance, components, reality) and the performance of workers in the technical college in Jeddah. With regard to the obstacles of the distance training, it was found that there is no direct correlational relationship of statistical significance between the distance training obstacles as one of the dimensions of the measure of distance training programs and the performance of workers in light of the Corona pandemic (Covid 19) In the Technical College in Jeddah, as there are no statistically significant differences due to the difference in demographic variables, and based on these results, the study recommended the adoption of adopting distance training programs as a strategic option within the human resources management strategy that contributes to the development and development of human resource capabilities in the college and keeps pace with rapid and urgent changes, whether economic, social or technological, which helps to raise individual and institutional performance. And communications that support the safe operation and flow of information to implement distance training programs that have the ability to deal with the largest number of workers, especially in light of the rapid development in information and communication technology, study distance training needs on an ongoing basis and pay attention to providing quality training programs aimed at developing the performance of employees Current and future, in addition to providing the institution with the necessary competencies and capabilities to achieve rapid rates in human resource development and achieving the desired goals.